Effects of Fishmeal or Urea Supplementation on Ruminal Fibre Digestion and Passage Kinetics in Bali Cows - Jelantik, IGN; Leo-Penu, C; Jeremias, J; Weisberjg, MR (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
Five non-pregnant Bali cows were used in a 5x5 latin square experimental design with the objective to study the effects of supplementation of graded levels of urea or fishmeal on fibre intake and digestion kinetics in Bali cows consuming low quality tropical grass hay. The animals were given ad libitum access to grass hay or supplemented daily with two levels of urea, i.e. 38 and 74 g, or two levels of fishmeal, i.e. 156 and 312 g. The measured parameters included were intake and apparent digestibility of DM and NDF, in sacco ruminal fibre degradation, and in vivo ruminal NDF digestion and passage kinetics. Intakes of DM and NDF were significantly improved by supplementation of both urea and fishmeal with fishmeal exerted a better effect at low level of supplementation. The increase of intake was mainly associated with the significant increase of rumen in sacco degradation of NDF. However, in vivo rumen digestions of NDF and DNDF were not significantly improved by supplementation due to the increased rumen pool of NDF after protein supplementation. As a result, rumen passage and digestion rates were not affected by supplementation. The effective level of fishmeal and urea supplementation to improve the intake of low quality fibrous tropical grass hay in Bali cows were 152 g/d and 74 g/d, respectively. (Animal Production 12(2): 74-81 (2010)Key Words: Bali cows, digestion kinetics, fishmeal, urea